2002
DOI: 10.1246/cl.2002.216
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Structure and Tribology of Calcium Lauroyl Taurate

Abstract: Calcium lauroyl taurate (C11H23CONH(CH2)2SO3·0.5Ca, CaLT) was synthesized, and the internal structure and tribology were studied. The powder of CaLT is a plate type crystal whose structure is lamellar at room temperature. When the powder is applied to an artificial skin, the frictional coefficient is lower than that for other solid lubricants. Such a high lubricity is caused by disintegration of the powder aggregates, cleavage of the lamellar layers, and deformation of the powder particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The adhesion energy between solid particles decreases with increasing hydrophobicity of the surfaces. Previously, we reported that a surfactant divalent metal salt, Ca salt of N-lauroyl taurate, forms a thin layer due to cleavage and disintegration; however, the lamellar structure still remained after deformation 5,6 . Conversely, C18:2 fatty acid Ca salt is not suitable for the absorption of frictional energy by cleavage due to its amorphous structure.…”
Section: Lubricant Properties Of Ca Salts Of Fatty Acidsmentioning
confidence: 98%
See 1 more Smart Citation
“…The adhesion energy between solid particles decreases with increasing hydrophobicity of the surfaces. Previously, we reported that a surfactant divalent metal salt, Ca salt of N-lauroyl taurate, forms a thin layer due to cleavage and disintegration; however, the lamellar structure still remained after deformation 5,6 . Conversely, C18:2 fatty acid Ca salt is not suitable for the absorption of frictional energy by cleavage due to its amorphous structure.…”
Section: Lubricant Properties Of Ca Salts Of Fatty Acidsmentioning
confidence: 98%
“…The difference between the lubrications of these three Ca salts of fatty acids is caused by their crystal structures. In the cases of C18:0 and C18:1 fatty acid Ca salts, the lubricity is due to three factors 5,6,13 . The first and second factors are cleavage of the lamellar layers and disintegration of the powder aggregates.…”
Section: Lubricant Properties Of Ca Salts Of Fatty Acidsmentioning
confidence: 99%
“…The adhesion energy between solid particles decreases with increasing hydrophobicity of the surfaces. Previously, we reported that one of surfactant divalent metal salts, N-lauroyl taurate Ca salt, forms a thin layer due to the cleavage and disintegration, although the lamellar structure still remained after the deformation 15,16 . The thin layer was hydrophobic: a water droplet formed a spherical lens on the layer.…”
Section: Lubricant Properties Of C16:1 Fatty Acid Ca Saltmentioning
confidence: 99%
“…The lubricity of surfactant divalent metal salts, including the C16:1 fatty acid Ca salt, is determined by three factors. The first and second factors are cleavage of the lamellar layers and disintegration of the powder aggregates 15,16 . These disruptions in the structural systems can absorb the friction force between solid surfaces.…”
Section: Lubricant Properties Of C16:1 Fatty Acid Ca Saltmentioning
confidence: 99%
“…Divalent metal salts of surfactants, known as "scum," are powdery materials used in many applications such as ingredients of lubricants and cosmetics, thermal stabilizers, water repellent agents, and fuel additives (Gregory and Spink, 1947;Morin and Briens, 2013;Nonomura et al, 2002aNonomura et al, , 2002bWendt and Wagner, 1954). Particularly, cosmetics and foods contain stearic acid calcium (Ca) salt, which is also used as a lubricant for powder formulations and anticaking agents.…”
Section: Introductionmentioning
confidence: 99%